Basic Methods for Diagnosing Non-Articular Pathology of the Temporomandibular Joint - Aliev Navruz Khasanovich (American Journal of Biology and Natural Sciences, 2024)
The article presents the results of studying the features of the biomechanics of the lower jaw in patients suffering from pain syndrome of the temporomandibular joints. Improving the efficiency of diagnosis and differentiation emphasizes the violation of the uneven nature of the pathology in patients with SBD TMJ.